2020
DOI: 10.3390/nano10122512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Ammonium Valeric Acid Iodide as Additive on Methyl Ammonium Lead Iodide Perovskite Solar Cells

Abstract: During the past decade, the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has risen rapidly, and it now approaches the record for single crystal silicon solar cells. However, these devices still suffer from a problem of stability. To improve PSC stability, two approaches have been notably developed: the use of additives and/or post-treatments that can strengthen perovskite structures and the use of a nontypical architecture where three mesoporous layers, including a porous carbon backconta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…[ 24 ] Three lifetimes of τ 1 , τ 2 , and τ 3 could be assigned to electron extraction, interface recombination, and bulk recombination, respectively. [ 25 ] We found that the introduction of BFN rarely changed the carrier lifetimes, especially the electron extraction lifetime τ 1 . The reason may be that BFN just located in a thin layer of perovskite near carbon electrode, which hardly influenced PL properties at the TiO 2 side.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] Three lifetimes of τ 1 , τ 2 , and τ 3 could be assigned to electron extraction, interface recombination, and bulk recombination, respectively. [ 25 ] We found that the introduction of BFN rarely changed the carrier lifetimes, especially the electron extraction lifetime τ 1 . The reason may be that BFN just located in a thin layer of perovskite near carbon electrode, which hardly influenced PL properties at the TiO 2 side.…”
Section: Resultsmentioning
confidence: 99%
“…x GABr denotes x mg·ml −1 GABr treatment in this work unless otherwise noted. The diffraction peaks at 14.08°, 28.42° and 31.88° corresponding to the (110), (220), and (330) planes of MAPbI 3 , and the peak at 12.78° is assigned to PbI 2 , which disappears after GABr treatment [ 37 , 38 ]. The intensity of MAPbI 3 peaks gradually increases at low concentrations of GABr, whereas when x is higher than 5, the intensity decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The photovoltaic properties of the resultant low-dimensional perovskites are greatly affected by the chemistry of the additive molecules, which then offer great potential for the preparation of perovskite materials with customized characteristics. Among the above-mentioned large cations, 5-AVA + has been employed as an excellent dopant to tailor the crystal structure of the absorber layer, resulting in an improved charge carrier lifetime . For example, Mei et al showed that the MAPbI 3 crystals were strengthened by 5-AVA + at the grain boundaries, and they indicated that the decomposition and ionic migration could be inhibited, meeting stability standards of IEC61215:2016 qualification tests for 9000 h .…”
Section: Introductionmentioning
confidence: 99%